Pengembangan Portal Web untuk Pengelolaan Informasi Publik Badan Usaha Milik Desa (BUMDes) Wonorejo - Andhika Putra Wardana; Fatah Yasin Al Irsyadi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Village-Owned Enterprises (BUMDes) play a vital role in improving community welfare through independent and professional village business management. One potential service is the provision of village internet, which supports digital transformation and information transparency. However, Wonorejo BUMDes still faces obstacles in managing these services, such as the ordering process and payment verification that have not been digitized. This study aims to design a web-based village internet service information system to improve transparency, efficiency, and public access to information. The system was developed using the Waterfall method, through the stages of needs analysis, design, implementation, testing, and evaluation and maintenance. The system was developed using the Laravel framework and tested using the Black Box Testing approach using 18 test scenarios (test cases), as well as the System Usability Scale (SUS) evaluation which produced a score of 77.44, which is included in the